2016
DOI: 10.1080/23311932.2016.1228732
|View full text |Cite
|
Sign up to set email alerts
|

Risk estimates for children and pregnant women exposed to mercury-contaminated Oreochromis niloticus and Lates niloticus in Lake Albert Uganda

Abstract: Exposure to mercury contaminated fish predisposes populations particularly children and pregnant women to various health hazards including neurotoxicity, reproductive abnormalities and cognitive disorders. Earlier studies in the Lake Albert community have demonstrated the presence of mercury in Nile tilapia and Nile perch. However, the risk estimates for vulnerable groups such as Children and pregnant women is not well documented. Secondary data-set from previous studies were employed comprising family househo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…Although the level of meHg in cephalopod and crustacean is lower compared to other marine fish, a high amount of consumption caused these groups of seafood to be significant contributors to meHg accumulation in adolescents in Peninsular Malaysia. Similar patterns of results were reported elsewhere, for example, Andrew et al (2016) demonstrated the disabilityadjusted life years (DALYs) for eating different parts of fish using a risk model (iRISK) and reported the frequency of consumption had exposed the children (< 17 years old) to noncarcinogenic risk, even the amount of Hg in fish part was minute. Their finding also showed that frequent access to tilapia fish in the community and district market attributed to more DALYs.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Although the level of meHg in cephalopod and crustacean is lower compared to other marine fish, a high amount of consumption caused these groups of seafood to be significant contributors to meHg accumulation in adolescents in Peninsular Malaysia. Similar patterns of results were reported elsewhere, for example, Andrew et al (2016) demonstrated the disabilityadjusted life years (DALYs) for eating different parts of fish using a risk model (iRISK) and reported the frequency of consumption had exposed the children (< 17 years old) to noncarcinogenic risk, even the amount of Hg in fish part was minute. Their finding also showed that frequent access to tilapia fish in the community and district market attributed to more DALYs.…”
Section: Discussionsupporting
confidence: 84%
“…MeHg can be concentrated in fish either directly in the water or through food chain components. The ingestion of fish contaminated with meHg has received considerable critical attention due to the adverse health outcomes of neurologic damage such as mental retardation, seizures, vision and hearing lost, delayed development, language disorder, and memory loss as well as renal damage, reproductive disorders, and damage in the cardiovascular system (Mehouel et al 2019;Andrew et al 2016;Barone et al 2015). MeHg could potentially be one of the risk factors for infertility (Hsi et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although level of meHg in cephalopod and crustacean is lower compared to other marine sh, but high amount of consumption caused these groups of seafood were signi cant contributors to meHg accumulation in adolescent in Peninsular Malaysia. Similar patterns of results were reported elsewhere, for example Andrew et al, (2016) demonstrated the Disability Adjusted Life Years (DALYs) for eating different part of sh using a risk model (iRISK) and reported the frequency of consumption had exposed the children (< 17 years old) to non-carcinogenic risk, even the amount of Hg in sh part were minute. Their nding also showed that frequent access to tilapia sh in the community and district market, attributed to more DALY's.…”
Section: Discussionsupporting
confidence: 82%
“…Choice of the oral reference dose is critical in determining the health risks the vulnerable community is exposed to, that is, use of the general population or vulnerable population oral reference dose [34]. The oral reference doses for mercury in the vulnerable and general population are 1 × 10 −4 and 3 × 10 −4 mg/kg per day, respectively [35,36]. Therefore, there is a need to send out a message to this vulnerable group about the health hazard they are encountering daily by consumption of food contaminated with mercury.…”
Section: Health Risk and Burden Due To Mercurymentioning
confidence: 99%